WOMEN LABOUR PARTICIPATION IN MGNREGA: A CASE STUDY - KAMLESHWAR PRASAD (International Journal of Multidisciplinary Research and Studies, 2020)
This is the most important reason for this. This "invisibility" of women's job is a key contributing factor to the fact that employment of women is not treated as a distinct activity in research or the creation of policy. The socially constructed gender ideologies contribute to this invisibility by creating a hierarchy in men's and women's roles, with men operating in the public domain, more specifically the market, and women being confined to the private domain, namely the household. This renders women's unpaid work "invisible," which ultimately leads to women's status being lower than that of men. The primary objective of the research done on FLFP has been to determine the factors that contribute to FLFP and its impact on a variety of issues, such as the amelioration of gender inequalities, the promotion of women's autonomy and independence, the protection of women and children, and other similar topics.